Social smart city research: interconnections between participatory governance, data privacy, artificial intelligence and ethical sustainable development - Samad Rasoulzadeh Aghdam; Samad Rasoulzadeh Aghdam; Behnaz Bababei Morad; Behnam Ghasemzadeh; Behnam Ghasemzadeh; Behnam Ghasemzadeh; Mazdak Irani; Aapo Huovila (Frontiers in Sustainable Cities)
Social aspects constitute both concerns and opportunities in smart city development, as evidenced by a rapidly increasing body of research. This article presents the first-ever review of all the existing research on social focus in smart cities, delineating the distribution of topics, knowledge bases, and research frontiers that constitute the existing body of knowledge. A bibliometric review was performed to pinpoint publication trends, influential authors, their institutions, and prevalent subject areas within the literature since 2000. Using the Web of Science database, an amalgamation of major indexes (SCI-EXPANDED, SSCI, AHCI, ESCI) were applied to consider the research pattern and citation impact in different disciplines. 1,030 selected articles were subjected to bibliometric mapping using VOSviewer. The results show an almost exponential growth in the number of publications from 2015 onwards. Four interconnected thematic clusters cropped up: (1) participatory governance, (2) data privacy and security, (3) artificial intelligence and social media, and (4) ethics and sustainable development. A deeper analysis of key terms used in recent research revealed the following hot topics: (1) governance and citizen participation, (2) artificial intelligence technologies such as machine learning, (3) blockchain, and (4) Internet of Things. Co-authorship and geographical analyses underpin a solid international collaboration for leading institutions. The results underscore the rising significance of social smart city research by emphasizing the interconnectedness of governance, technology, citizen engagement, and ethics for a comprehensive approach to smart city initiatives. Furthermore, they recommend integrating social equity into these frameworks and enhancing geographic studies through greater international collaboration.